Manifestações bucais da sífilis: estudo retrospectivo - Guidi, Rafaela (2007)
The aim of this study was to assess the occurrence of syphilis and its oral manifestations in patients attended in a teaching hospital of a medical school in Uberlândia, Brazil, between 1999 and 2006, in view of its recent resurgence related in Europe, Unites States and Latin America and the current worry about spreading during the practice of dentistry. At the period of this study, 1,229,964 patients were attended at the teaching hospital witch 298 has confirmed diagnosis of syphilis in all clinical forms, by clinical and laboratorial findings. We have collected epidemiological data including gender, age, race, origin, stage of occurrence and oral manifestations. Data was subjected to descriptive and statistical evaluation. Results demonstrate that of the 289 syphilis cases, 99 was congenital syphilis and 199 acquired syphilis. Of these 199 cases, 101 were male and the mean age was 36,5 years (range, 16-81 years). The majority of cases were white (57%). Acquired syphilis showed 5 cases as primary syphilis (2,5%), 33 cases as secondary(16,5%), 49 cases as latent (25%), 8 cases as tertiary (4%) and 87 cases as treated(44%). Among these cases, 5% presented with oral manifestations and 13,5% of cases were HIV positive. The occurrence of syphilis, in the studied population was only 0,024% and variation was statistically significant between 2004 and 2005, in which a decrease was noted. The percentual of oral manifestations when cases of latent and treated syphilis (asymptomatic disease) was excluded, achieved 15,8%. The high prevalence of congenital syphilis can reflect the diagnosis efforts, since the implantation of congenital syphilis eradication program by the Brazilian Health Department. Considering the rarity of nonsexual transmission of syphilis and the low percentual of cases in our sample, we believe that contagion and dissemination risk during the practice of dentistry is low in studied population.